Building and Sustaining National ICT Education Agencies : Lessons from International Experiences - Trucano, Michael (World Bank, Washington, DC, 2017)
National ICT/education agencies (and their functional equivalents) play important roles in the implementation and oversight of large scale initiatives related to the use of information and communication technologies in education in many countries. That said, little is known at a global level about the way these organizations operate, how they are structured, and how they typically evolve over time. Through an examination of lessons from the development and history of a set of representative ICT/education agencies in East Asia, and, to better understand East Asian experience, other countries around the work, this paper seeks to identify common challenges and issues and potential relevance to leaders of such institutions.